2019
DOI: 10.15809/irriga.2019v24n1p69-85
|View full text |Cite
|
Sign up to set email alerts
|

Reposição Deficitária De Água E Adubação Com Organomineral No Crescimento E Produção De Tomateiro Industrial

Abstract: REPOSIÇÃO DEFICITÁRIA DE ÁGUA E ADUBAÇÃO COM ORGANOMINERAL NO CRESCIMENTO E PRODUÇÃO DE TOMATEIRO INDUSTRIAL*     MARCELO JOSÉ DE ALMEIDA1; CLEITON MATEUS SOUSA2; MARIELLA CAMARGO ROCHA3; VINÍCIUS DE MELO BENITES4 E JOSÉ CARLOS POLIDORO5   * Parte da Dissertação do primeiro autor apresentada no Programa de Pós-Graduação em Irrigação no Cerrado 1 Mestre em Irrigação no Cerrado, Programa de Pós-Graduação em Irrigação no Cerrado, Instituto Federal de Educação, Ciência e Tecnolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
1
2
0
2
Order By: Relevance
“…Under favorable conditions, plants prioritize vegetative development since it is the acquired vegetative mass that supplies the need for photoassimilates that fruits demand when they start to appear. Therefore, a well-nourished plant can produce greater amounts of photoassimilates which later results into growth in height (BATISTA et al, 2015;ALMEIDA et al, 2019). The results found in this work supports this idea, in which, regardless of the source used, greater values of PH were observed when P was applied.…”
Section: Resultssupporting
confidence: 76%
“…Under favorable conditions, plants prioritize vegetative development since it is the acquired vegetative mass that supplies the need for photoassimilates that fruits demand when they start to appear. Therefore, a well-nourished plant can produce greater amounts of photoassimilates which later results into growth in height (BATISTA et al, 2015;ALMEIDA et al, 2019). The results found in this work supports this idea, in which, regardless of the source used, greater values of PH were observed when P was applied.…”
Section: Resultssupporting
confidence: 76%
“…Fruit growth is affected by the water status (Soares et al, 2011), thus, decreases in fruit growth and size are connected to daily increases or decreases in plant water potential and soil water contents. When receiving organomineral fertilization, tomato plants grow more, ensuring a better nutritional balance in their tissues and favoring the transport of photoassimilates, water and nutrients, which improves fruit quality (Almeida et al, 2019;Peres et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…2017) evaluated the response of tomato plants to applications of different soil fertilizers and found that the use of mineral fertilizer resulted in the largest FTD, and the use of organic fertilizer resulted in the largest FLD. Thus, the presence of organic matter with mineral nutrients in organomineral fertilizers promotes the absorption and helps in the transport of photoassimilates produced by the plant itself (Almeida et al, 2019). The slow release of nutrients occurs in organominerals, which tends to persist for a longer period in the soil (Aguilar et al, 2019;Souza et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A maior disponibilidade de Mg e Zn pela formulação com organomineral+K2SO4 na ausência de ácidos húmicos e fúlvicos (Tabela 12), comprova a alta eficiência desses fertilizantes no incremento da matéria orgânica ao solo, no aumento da disponibilidade de fósforo ou equivalência aos minerais que estão disponíveis no mercado com os testados no estudo, KCl e MAP (Tabela 13), e por mais que não foi analisado neste estudo, o nitrogênio disponível é afetado positivamente pela fertilização com organomineral de forma geral, pois a matéria orgânica presente no material, promove redução da atividade de enzimas no solo e reduz a perda de nitrogênio pela dinâmica de comportamento do NH4 + (Almeida et al, 2019).…”
Section: Característicasunclassified
“…Desta maneira, o uso de fertilizante organomineral como fonte de nutrientes e condicionadores do solo, tem sido alvo de estudos sobre alternativas viáveis de adubação das culturas com preservação da qualidade ambiental (Almeida et al,2019).…”
Section: Introductionunclassified